Three-Dimensional Physical Simulation and Control Technology of Roof Movement Characteristics in Non-Pillar Gob-Side Entry Retaining by Roof Cutting - Xinzhu Hua; Guanfeng Chang; Xiao Liu; Bingjun Sun; Sen Yang; Enqian Wang; Chen Li (Shock and Vibration)
An overlying rock structure plays a key role in controlling the roof deformation of nonpillar gob-side entry retaining by roof cutting. On the bases of the actual geological conditions of II 632 Haulage Roadway at the Hengyuan coal mine, a similar three-dimensional simulation experiment of roof precutting is conducted. Thereafter, the caving characteristics and migration law of the roof strata in the strike and dip directions are obtained. Moreover, the roof of the retained roadway and key strata of the goaf can form a hinge structure of the key blocks. By monitoring the deformation of the surrounding rock and stress distribution of the roof, the skew deformation characteristics of roadway roof are obtained. By observing the borehole peeping technology, the roof subsidence near the goaf is determined to be greater than that of the solid coal side, and the roof subsidence of the gob-side entry retained by roof cutting is greater than that of the floor heave and two sides approaching. Results of the three-dimensional similar simulation experiment indicate that the mechanical structure model of the key block of the retained roadway roof is constructed, and the mechanical analytical solution of the required support resistance of the retained roadway roof is obtained. This study proposes the constant resistance and large deformation anchor cable reinforcement support method to control the roof deformation of the retaining roadway. Through engineering application, the maximum value of the roof and floor movement of the retained roadway is stable at approximately 650 mm. The retained roadway can meet the demand of the next mining face.